Big Data in Digital Transformation of Corporate Marketing Strategy - Ramadhani, Razika (Economic and Business Horizon, 2024)
Business transformation in the digital era has become an urgent need for companies that want to increase their competitiveness. Technological advances have brought significant changes in marketing strategies, enabling a smarter, more efficient, and responsive approach to market changes. This study aims to analyze the role of technologies such as big data, Artificial Intelligence (AI), and marketing automation in increasing the effectiveness of digital marketing. Using a literature study method, this study examines various academic and industry sources to understand how companies can optimize technology in their marketing strategies. The results of the study show that the success of business transformation depends not only on the adoption of technology but also on the readiness of the organization and a culture of innovation that supports change. Therefore, companies need to continue to develop digital capabilities and adapt to technological trends to stay competitive in a dynamic market.